Mechanical Properties Of Reclaimed Asphalt Pavement Mixtures With Rejuvenator - Ong, Ju Kit (Universiti Sains Malaysia, 2018)
In view of the ever-escalating demand for virgin aggregates and bitumen, research efforts have now turned to reclaimed asphalt pavement (RAP) technology as the solution for sustainable bituminous road construction. However, substituting virgin materials with very high RAP contents would render the pavement vulnerable to cracking. Thus, rejuvenator is incorporated to recuperate the performance of RAP mixtures. The primary objective of this study is to investigate the effects of a rejuvenator on the mechanical properties of asphalt mixtures incorporating 50% and 70% RAP contents in terms of cracking and rut susceptibility. This study compares the performance of RAP mixture with virgin mixture imparted with a strong antistripping agent. Overall, conventional performance tests such as resilient modulus, indirect tensile strength and notched SCB tests indicated that the rejuvenated mixtures performed comparably with virgin mixtures, and outperformed non-rejuvenated RAP mixtures in the context of pure tensile and tensile-shear fracture toughness and elastic deformation. Through algorithmic modelling, it was also found that rejuvenated mixtures experienced relatively earlier stripping in comparison with virgin and non-rejuvenated RAP mixtures in the dynamic creep test. A new two-dimensional (2-D) imaging technique was innovated to better understand the effects of rejuvenator on the stiffness of RAP mixtures in various fracture tests. Image analysis was implemented with the use of geographic information system (GIS) software. From this study, 2-D imaging technique revealed that the fracture path and tensile strength of asphalt mixtures were governed by the stiffness of the mortar layer at intermediate temperature, but influenced by the strength of aggregates at lowtemperature. The effects of rejuvenator on the fracture surface characteristics of RAP mixtures were found to be significant.